A inclusão de crianças com TDAH na escola pública: um estudo de caso na E.M.E.I.E.F. “Rotary” - COIMBRA, Renata Gabriele Ferreira (2019)
This Work of Conclusion of Course (TCC) emphasized the theme "School Inclusion of Children with Attention Deficit / Hyperactivity (ADHD) in a Municipal public school of Belém-PA" and it is specifically of the type case study. The collection of data from this CBT was done at the Municipal School of Early Childhood Education and Rotary Elementary during my internship as a scholar of the Project "Teacher Training for an Inclusive School: Collaborative Actions between Higher Education and Basic Education in Parish Counties "Of the Study and Research Group INCLUDERE, which was funded by the Institutional Scholarship Initiative Program (PIBID), which occurred in 2017. Thus, the purpose of this work was directed to" The School Inclusion of Children with ADHD in Initial Years of Elementary Education at EMEIEF Rotary, of the Municipality of Belém-PA ". The general objective of this work was to understand how school inclusion of children with ADHD was occurring in the Early Years of Primary Education in E.M.E.I.E.F. "Rotary." The specific objectives of this research, based on the area's theorists, have tried to: Defined and characterize what ADHD is; To identify theoretical proposals about the inclusion of children with ADHD in schools; and finally, Analyze what the school was doing to ensure the inclusion of children with ADHD in the initial years of elementary school, this was done through an interview with some regular classroom teachers and documentary analysis through the Political Pedagogical Project (PPP) of said school. With this study, it was possible to conclude that the educational process of children with ADHD as well as their inclusion in E.M.E.I.E.F. "Rotary," still "walks" to what is expected to be true about School Inclusion of Children with (ADHD) in Public School. The study concluded that E.M.E.I.E.F. "Rotary" promotes practices largely in the nature of attempts at: inclusion, appropriateness, methodologies ... It is also concluded from this field research that effective school-based assistance to teachers is lacking. In view of these conclusions, it was perceived that there is in this school an "exclusion-excluding", since the school receives these students with special educational needs, but these subjects are considerably ignored and still lack a process of quality schooling. It was also possible to conclude that the researched school needs theoretical and practical changes on the subject, since the theme of inclusion still lacks a greater debate within the public schools and, therefore, convince the school community that an inclusive school is a school that respects the particularities of the subjects that enter it and that the subject also requires permanent formations involving not only the teachers of children with ADHD, but all other members of the collective of the unit of education, since the school inclusion requires collaboration of all.